2019
DOI: 10.3390/s19112440
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Learning-Based Physical Layer Authentication for Industrial Wireless Sensor Networks

Abstract: In this paper, a deep learning (DL)-based physical (PHY) layer authentication framework is proposed to enhance the security of industrial wireless sensor networks (IWSNs). Three algorithms, the deep neural network (DNN)-based sensor nodes’ authentication method, the convolutional neural network (CNN)-based sensor nodes’ authentication method, and the convolution preprocessing neural network (CPNN)-based sensor nodes’ authentication method, have been adopted to implement the PHY-layer authentication in IWSNs. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 30 publications
0
50
0
Order By: Relevance
“…Authors have used the received CSI and known locations of wireless transmitters as input to machine learning systems that are then used to accurately determine the position of the transmitters at a later time [33], [34], [35]. Additionally, there has been physical-layer authentication research based on CSI using spatial information and machine learning [36], [37], [38], [39]. Pan et al showed that static environments, rich fading, and antennas separated by greater than a half wavelength improved authentication performance [39].…”
Section: Related Workmentioning
confidence: 99%
“…Authors have used the received CSI and known locations of wireless transmitters as input to machine learning systems that are then used to accurately determine the position of the transmitters at a later time [33], [34], [35]. Additionally, there has been physical-layer authentication research based on CSI using spatial information and machine learning [36], [37], [38], [39]. Pan et al showed that static environments, rich fading, and antennas separated by greater than a half wavelength improved authentication performance [39].…”
Section: Related Workmentioning
confidence: 99%
“…In paper [142], in order to improve the secure operation of industrial wireless sensor networks (IWSNs), a physical layer authentication based on deep learning is presented. Three different authentication methods for sensor nodes, more specifically the deep neural network (DNN), the convolutional neural network (CNN) and convolution pre-processing neural network (CPNN) have been used to deploy the PHY-layer authentication in IWSNs.…”
Section: A Review Of Articles For Special Issue On Green Energy-ementioning
confidence: 99%
“…Reference [17] proposes a threshold-free physical layer authentication scheme based on machine learning, which improves the detection accuracy without increasing the amount of calculation. To detect the spoofers, [18] presents several adaptive moment estimation algorithms based on deep neural network for lightweight authentication, which can accelerate the training of the authentication model and guarantee extremely low latency. Similarly, neural networks proposed in [19] are used to optimize the encoding and decoding functions, and to learn the trade-off between reliable communication and information secrecy to distinguish eavesdroppers.…”
Section: Related Workmentioning
confidence: 99%